2013
DOI: 10.1007/s11695-013-0894-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Bypass and Sleeve Gastrectomy: the Same Impact on IL-6 and TNF-α. Prospective Clinical Trial

Abstract: RYGB and SG procedures demonstrated a similar impact on adipokine levels in women 1 year post-surgery. Both techniques may improve the course of chronic diseases and the state of inflammation associated with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 46 publications
9
47
0
Order By: Relevance
“…The LRYGB-induced decline in biomarkers of systemic inflammation is wellestablished in available literature (9)(10)(11)(12) . Our results identify a time-course of changes in pro-and anti-inflammatory cytokines with potentially relevant pathophysiological implications.…”
Section: Basalmentioning
confidence: 95%
See 1 more Smart Citation
“…The LRYGB-induced decline in biomarkers of systemic inflammation is wellestablished in available literature (9)(10)(11)(12) . Our results identify a time-course of changes in pro-and anti-inflammatory cytokines with potentially relevant pathophysiological implications.…”
Section: Basalmentioning
confidence: 95%
“…Proinflammatory changes in circulating cytokines are thought to contribute to obesity-associated morbidity by favoring the onset of insulin resistance and cardiovascular dysfunction (5)(6)(7) . Weight loss induced by caloric restriction or bariatric surgery may limit these alterations (7)(8)(9)(10)(11)(12) , and these effects may contribute to the positive effect of weight loss to reduce obesityassociated morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Adipokines, a diverse class of biologically active compounds released by adipose tissue mediate a host of physiological processes including inflammation and glucose and lipid metabolism, play a crucial role in the metabolic effects of obesity and its associated comorbidities [48,49]. However, it is well established that bariatric surgery restores, at least partially, inflammatory adipokine regulation, with studies describing an overall decrease in pro-inflammatory adipokines, such as IL-6 and TNF-α, and an increase in anti-inflammatory adipokines such as adiponectin following RYGB and/or VSG up to one year following the procedure [50][51][52][53][54][55]. Strikingly, there are some discrepancies in the values of C-reactive protein (CRP), a pro-inflammatory adipokine, following bariatric surgery, with both significant increases and decreases results reported [51][52][53][55][56][57].…”
Section: Potential Mechanisms Leading To Weight Loss and Improved Diamentioning
confidence: 99%
“…On the contrary, systemic and adipose-tissue inflammation seems to decrease following bariatric procedures both at the biochemical and at the clinical level. These changes supposedly promote risk reduction in obesity-associated comorbid conditions including T2DM, cardiovascular diseases, infections, and cancer [20,21,22,23]. …”
Section: Bs and Inflammationmentioning
confidence: 99%
“…Viana et al [20] demonstrated a significant decrease in systemic inflammatory cytokines (IL-6 and TNF-α) 1 year after RYGBP and SG. Sams et al [21] found a significant and rapid increase in subcutaneous adipose anti-inflammatory cytokines (e.g.…”
Section: Bs and Inflammationmentioning
confidence: 99%